2011
DOI: 10.1007/s10342-011-0573-6
|View full text |Cite
|
Sign up to set email alerts
|

Model-based analysis of the spatial variability and long-term trends of soil drought at Scots pine stands in northeastern Germany

Abstract: Soil water availability determines the vitality of trees and forest stands to a large degree. Over the last decades, an increasing number of drought spells has been observed in several parts of Europe. Our study aims to estimate long-term trends of soil drought at Scots pine (Pinus sylvestris L.) stands along the prevailing climatic gradient in Mecklenburg-Western Pomerania, northeastern Germany. To this end, soil water balance simulations were carried out at 24 sites over the period from 1951 to 2009 with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The LWFBrook90 model has undergone testing, refinement, and validation over several years by several researchers. Many studies (Baumgarten et al, 2014; Bauwe et al, 2012; Schwärzel et al, 2009) have shown the ability of the LWFBrook90 model to simulate hydrological processes in different ecosystems. This study selected LWFBrook90 model because of its improved performance; it provides submodels for model parameterization and facilitates parallel computing, sensitivity analysis, and inverse calibration of the model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LWFBrook90 model has undergone testing, refinement, and validation over several years by several researchers. Many studies (Baumgarten et al, 2014; Bauwe et al, 2012; Schwärzel et al, 2009) have shown the ability of the LWFBrook90 model to simulate hydrological processes in different ecosystems. This study selected LWFBrook90 model because of its improved performance; it provides submodels for model parameterization and facilitates parallel computing, sensitivity analysis, and inverse calibration of the model.…”
Section: Methodsmentioning
confidence: 99%
“…The LWFBrook90 model has undergone testing, refinement, and validation over several years by several researchers. Many studies (Baumgarten et al, 2014;Bauwe et al, 2012;Schwärzel et al, 2009)…”
Section: Lwfbrook90 Model Descriptionmentioning
confidence: 99%
“…For soil moisture movement, the model uses the Van Genuchten equation and Brooks Corey equation to calculate soil hydraulic parameters, and uses the Darcy Richards equation to simulate soil moisture movement [33]. The LWFBrook90 model exhibits superiority in simulating hydrological processes in different ecosystems because of its improved performance, providing submodels for model parameterization and facilitating parallel computations [33][34][35]. The LWFBrook90 model was also previously applied to successfully simulate the water-balance components of tea plantations and bamboo forests in our study area [9].…”
Section: Description Of the Lwfbrook90 And Biome-bgc Modelsmentioning
confidence: 99%
“…As a consequence, EFIMOD is not able to simulate, for example, the negative effect of drought stress on productivity (Martínez-Vilalta et al 2008;Huang et al 2010;Hartmann 2011;Bauwe et al 2012). We believe that introducing a more detailed ecophysiological model to our simulation experiments will deliver more clarity to this issue.…”
Section: Verification Of the Model And Analysis Of Uncertaintiesmentioning
confidence: 99%